Impact of Animated Health Education on Mothers' Knowledge of Febrile Seizure Management in Toddlers - Nur, Zainatul Arusaini (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2024)
Improper handling of children with febrile seizures has an impact on the occurrence of recurrent febrile seizures or complications can occur. Several factors influence a person's knowledge, namely the provision of health education. Supporting media is important in delivering health education. The purpose of this study was to analyze the effect of health education on the level of mother's knowledge about the cruel treatment of fever in toddlers. The research design was (one-group pre-post test design). The number of samples in this study were 54 mothers who came to Posyandu Dahlia, Kerjen Village. This research was conducted on May 10, 2023. The research instrument used SAP, animated videos and pre-test questionnaires. The results of this study show that based on the results of the Wilcoxon Signed Rank Test statistical test at the pretest and post-test a p-value of 0.000 or <0.05, then Ho was rejected and Ha was accepted, which means that there is an influence in providing health education using animated videos on the level of mother's knowledge about handling febrile seizures in toddlers. It is hoped that the results of this study can be used as material for evaluation and information in supporting Pediatric Nursing regarding the management of damam seizures in toddlers.Keywords: Knowledge, media, febrile seizure